Proximalisation in the acquisition of sign language by hearing adult learners - Chambers, Dana (My University, 2023)
This research study explores whether or not proximalisation is present in the acquisition of South African Sign Language (SASL) by hearing adult learners. This research will specifically be looking at the extent of proximalisation, as well as the details of how and when proximalisation occurs. This research is motivated by the fact that while both the study and the use of sign language by hearing people is growing on a global scale there is very little research done on their production using the necessary joints. I have used a quantitative descriptive study in order to investigate the presence of proximalisation in the signs produced by hearing learners. I have used the study done by Mirus, Rathmann and Meier (2001) who looked at the proximalisation and distalisation of German Sign Language and American Sign Language as a basis for this research study. This study focused on the proximalisation in the production of signs by hearing adult first year SASL learners with no prior knowledge of sign language. I have also used a study by Napoli et al (2014) to identify additional features regarding joint usage and joint manipulation in regards to ease of articulation. Based on the findings by Mirus, Rathmann and Meier (2001) in their study the findings of this study show a significantly lower than expected presence of proximalisation. It was found that participants joint manipulation rather favoured that of distalisation, joint omission (the complete lack of the joint in the production) and joint addition. These were unexpected and all resulted in an ease of articulation and overall, less energy and effort production.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, at the University of the Witwatersrand, Johannesburg, 2023